2010
DOI: 10.1002/rnc.1502
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of reset control systems

Abstract: In this paper we present a general linear matrix inequality-based analysis method to determine the performance of a SISO reset control system in both the L 2 gain and H 2 sense. In particular, we derive convex optimization problems in terms of LMIs to compute an upperbound on the L 2 gain performance and the H 2 norm, using dissipativity theory with piecewise quadratic Lyapunov functions. The results are applicable to for all LTI plants and linear-based reset controllers, thereby generalizing the available res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 28 publications
0
78
0
Order By: Relevance
“…See also Beker et al (2004); Nesić et al (2008) where reset controllers are used to decrease the L 2 gain between perturbations and the output. Consider also Aangenent et al (2010) where it is shown that reset con-1 Work supported by the ANR project ArHyCo, ARPEGE, contract number ANR-2008 SEGI 004 01-30011459, and by HYCON2 Network of Excellence "Highly-Complex and Networked Control Systems", grant agreement 257462. christophe.prieur@gipsa-lab.fr sophie.tarbouriech@laas.fr zaccarian@laas.fr trollers may be useful to improve the L 2 or H 2 stability of linear systems. Finally, see Lazar and Heemels (2009) for the design of predictive controllers for the input-tostate stability of hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…See also Beker et al (2004); Nesić et al (2008) where reset controllers are used to decrease the L 2 gain between perturbations and the output. Consider also Aangenent et al (2010) where it is shown that reset con-1 Work supported by the ANR project ArHyCo, ARPEGE, contract number ANR-2008 SEGI 004 01-30011459, and by HYCON2 Network of Excellence "Highly-Complex and Networked Control Systems", grant agreement 257462. christophe.prieur@gipsa-lab.fr sophie.tarbouriech@laas.fr zaccarian@laas.fr trollers may be useful to improve the L 2 or H 2 stability of linear systems. Finally, see Lazar and Heemels (2009) for the design of predictive controllers for the input-tostate stability of hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing resets has advantages and disadvantages, as pointed out in Aangenent et al (2010). Indeed, the performance improvements of resets controllers with respect to continuous dynamics branch out even to the possibility of using controller dynamics that exponentially destabilize the continuous-time closed loop without resets (see Section 4).…”
Section: Propositionmentioning
confidence: 99%
“…This fact might be important to keep in mind when embedding reset passivation rules. Of course, as underlined in Aangenent et al (2010), providing fully constructive synthesis tools for reset controllers is an open research problem.…”
Section: Propositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stability of reset control systems is a main concern from a theoretical and practical point of view, and several recent works have approached the stability problem. See for example [6][7][8], and the works [9][10][11].…”
Section: Introductionmentioning
confidence: 98%